Pemetaan Penelitian Pendidikan Anak Usia Dini: Analisis dan Mapping Publikasi Hasil Penelitian pada Jurnal Golden Age - Purnama, Sigit; 'Aziz, Hafidh; Abdul Latif, Muhammad; Mustamid, Mustamid; Suismanto, Suismanto (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
This study aims to map the distribution of research in the field of early childhood education based on author affiliation, methodology and research themes. This research uses a qualitative descriptive approach with data collection techniques used in the research is documentation or document review, supported by interviews to find out the publication of research results in the Golden Age Journal, whether it is in accordance with scientific journal accreditation standards and building research mapping and scientific journal publications. With the Content Analysis, the following results were found: The Golden Age Journal has also implemented online journal management using the Open Journal System (OJS) version 3, by referring to the national journal accreditation guidelines, but it has not fully met the journal accreditation standards so it needs to be improved, by expanding it. the aspirations of the area both authors and managers, as well as the development of research themes that have good novelty.